2021
DOI: 10.1016/j.gfs.2020.100463
|View full text |Cite
|
Sign up to set email alerts
|

The Zoonotic diseases, agricultural production, and impact channels: Evidence from China

Abstract: The outbreak and wide spread of COVID-19 poses a new threat to global food security. This paper aims to address two important policy related issues, that is which agricultural subsector suffers more under zoonotic diseases and how do zoonotic diseases affect these subsectors. Using provincial panel data of 24 main farm commodities in China from 2002 to 2017, this paper identifies the impacts of zoonotic diseases and projects the potential disruption of COVID-19 to agricultural output in China under three scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although several special issues are expected to be available in the coming months, most of the information available at the time of writing is on impacts of the health crisis and containment measures and potential mechanisms to mitigate the impacts ( Adhikari et al, 2021 ; Kumar et al, 2021 ). A few papers focused on interventions that respond to specific component of the food system, such as seed systems, agricultural production, and trade ( Sperling, 2020 ; Gong et al, 2021 ; Amjath-Babu et al, 2020 ; Pu and Zhong, 2020 ; Chen and Mao, 2020 ). We expect that China's experiences could improve understanding of the challenges posed by COVID-19 from a retrospective perspective and provide lessons to other countries that are experiencing disruptions in the agri-food system.…”
Section: Introductionmentioning
confidence: 99%
“…Although several special issues are expected to be available in the coming months, most of the information available at the time of writing is on impacts of the health crisis and containment measures and potential mechanisms to mitigate the impacts ( Adhikari et al, 2021 ; Kumar et al, 2021 ). A few papers focused on interventions that respond to specific component of the food system, such as seed systems, agricultural production, and trade ( Sperling, 2020 ; Gong et al, 2021 ; Amjath-Babu et al, 2020 ; Pu and Zhong, 2020 ; Chen and Mao, 2020 ). We expect that China's experiences could improve understanding of the challenges posed by COVID-19 from a retrospective perspective and provide lessons to other countries that are experiencing disruptions in the agri-food system.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical data of 2020 revealed that the pandemic substantially decreased approximately 147 million full-time jobs which resulted in an economic loss of 3.8 billion dollars globally (Agovino and Gaetano 2022). Since 2020, COVID-19 collapsed the livestock as well as crop industries of China by about 2.3% and 1.1% respectively (Gong et al 2021). Similarly, in 2014, the Ebola virus adversely affected the production of coffee (50%) and rice production (20%) in Ghana, thus ultimately reducing the agricultural economic growth (Zhang et al 2020).…”
Section: Assessment Of Economic Losses Due To Zoonotic Diseasesmentioning
confidence: 99%
“…Proper allocation of factors has the potential to increase grain output and alleviate the structural contradiction between grain production and demand [4], thereby stimulating farmers' enthusiasm for grain cultivation. Despite utilizing only 9% of the world's arable land to feed nearly 20% of the population, China has achieved remarkable success in global food production [5]. Therefore, this study focuses on China to explore whether there is factor misallocation in its agricultural production sector and its implications for food security.…”
Section: Introductionmentioning
confidence: 99%